The place of musie in thepoetry of Kazimierz Przerwa-Tetmajer - Bajda, Justyna (Interdisciplinary Studies in Musicology, 2018)
Young Poland poetry was dominated by artistic imaging, but its associations with music are also quite often mentioned. Many examples of its “musicality” can be found in various layers of poetic works, starting with their phonological aspect and versification, through the simple usage of lexical resources, descriptions of instruments and concerts and listeners’ impressions, up to attempts at finding appropriate means for transposing particular genres or specific musical works into poetry and even creating a poetic language modelled on music. The characteristic phenomenon of poetry challenging music can be observed during that period. The oeuvre of Fryderyk Chopin is especially important, as there are many sets of works concerned with Chopin’s music or the composer himself (about 150). Kazimierz Przerwa-Tetmajer was one of the Young Poland poets to show an interest in this subject. The images created by Tetmajer’s specific artistic imagination were often defined by elements of a musical character. The best-known “musical” set of works by Tetmajer is the Preludes, considered to be his “calling-card”. Tetmajer used sounds in many different ways. Besides attempts at shaping this poetical cycle in the image of Chopin’s preludes, one should mention here the role of the music and songs of the highlanders, the repetitive distant chime of church bells, the various musical instruments, notes and tones reverberating in many poems, and the specific role of the music of nature. The works directly inspired by Fryderyk Chopin’s music (Mazurek Chopina [Chopin’s mazurka], Cień Chopina [Chopin’s shadow], Zamyślenia XVI [Thoughtfulness XVI]) are a good reflection of Tetmajer’s way of thinking and writing about the sounds of nature. They are part of the tum-of-the-century mood, since they use impressionistic, symbolic and pre-Raphaelite poetics. The poem Zamyślenia provides a sort of conclusion to Tetmajer’s poetical thinking about Chopin, and about music in general. The poet agrees here with the modernist vision of Chopin as a bard of the nation. Almost all the leitmotifs favoured by the poet and connected to his perception of music appear here: the effect of “listening” to sounds from afar, a soul filled with grief (reminiscent of the sad tones of the music), a mood encompassing the whole universe and moving deep layers of human sensitivity, specifically among Poles.